Nanomedicine's shining armor: understanding and leveraging the metal-phenolic networks - Zhengming Tang; Zhijie Huang; Yisheng Huang; Mingshu Huang; Hongyu Liu; JianZhong Du; Bo Jia (Journal of Nanobiotechnology)
Abstract Metal-phenolic networks (MPNs), which comprise supramolecular amorphous networks formed by interlinking polyphenols with metal ions, garner escalating interest within the realm of nanomedicine. Presently, a comprehensive synthesis of the cumulative research advancements and utilizations of MPNs in nanomedicine remains absent. Thus, this review endeavors to firstly delineate the characteristic polyphenols, metal ions, and their intricate interaction modalities within MPNs. Subsequently, it elucidates the merits and demerits of diverse synthesis methodologies employed for MPNs, alongside exploring their potential functional attributes. Furthermore, it consolidates the diverse applications of MPNs across various nanomedical domains encompassing tumor therapy, antimicrobial interventions, medical imaging, among others. Moreover, a meticulous exposition of the journey of MPNs from their ingress into the human body to eventual excretion is provided. Lastly, the persistent challenges and promising avenues pertaining to MPNs are delineated. Hence, this review offering a comprehensive exposition on the current advancements of MPNs in nanomedicine, consequently offering indirect insights into their potential clinical implementation. Graphical Abstract